FAKTOR-FAKTOR YANG DIPERTIMBANGKAN DALAM KEPUTUSAN PEMBELIAN MINYAK GORENG BIMOLI PADA IBU RUMAH TANGGA DESA KEBONAGUNG KECAMATAN PURWOREJO KOTA PASURUAN - Bukhori, Mochamad; Ekasari, Tutik (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
Consumer behavior towards purchasing decisions is something that should be studied by marketers to know and understand how consumers make decisions, and the extent to which marketing stimuli can provide stimulation to the purchasing decision. So they can know what are the factors that influence consumer purchasing decisions. The purpose of this study was to determine the factors that are considered in the purchase decision of cooking oil Bimoli housewives Kebonagung Village District Purworejo Pasuruan. Population and sample in this study were housewives Kebonagung Village District Purworejo Town of Pasuruan who bought and used cooking oil Bimoli. The number of samples is determined using a quota sampling of 50 respondents, the sampling technique used purposive sampling. Methods of data collection using observation, interviews, and questionnaires. Analyzed using factor analysis to test the hypothesis. The results showed that of the eight factors suspected to be considered in the purchase decision, there are five factors that influence purchasing decisions, namely: price factors, social factors, psychological factors, distribution factors, and personal factors.